The Two Stay Two Stray Method for Developing Interpersonal Communication - Dea Maulita Putri Rico; Siti Fitriana; Farikha Wahyu Lestari (Bisma The Journal of Counseling, 2019)
This research is motivated by students who are unable to appreciate friends or other people who are talking, cannot be good listeners, do not speak when meeting other people on the street, do not shake hands with the teacher they meet, students are less able to communicate in good language to the teacher or friend, unable to respond properly when invited to speak. This type of research is a quantitative research design of quasi-experimental from nonequivalent control group design with the pre-test model post-test control group design. The population of this research is the students of class XI Accounting 1, XI Marketing 2, XI Animation SMK Muhammadiyah 1 Semarang. The sampling used in this study is Simple Random Sampling. The data analysis technique used is percentage analysis with t-test. The results of the interpersonal communication scale of the experimental group using the t-test post-test results showed an average of the experimental group of 79.5% and the control group of 71.23%. So that there was an increase in the experimental group by 8.27%. In the calculation of the t-test results obtained at the count (12.99)> t table (2.00). Then the working hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. It was concluded that there was an influence of classical guidance with the two stay two stray method on interpersonal communication of class XI students of SMK Muhammadiyah 1 Semarang.